Enterocin CRL35 Inhibits Listeria monocytogenes in a Murine Model - Salvucci, Emiliano Jesus (2011)
Listeria monocytogenes is a foodborne pathogen causative of opportunistic infections. Listeriosis is associated with severe infections in pregnant women causing abortion or neonatal listeriosis. An alternative to antibiotics are safe novel bacteriocins peptides such as enterocin CRL35 with strong antilisterial activity produced by Enterococcus mundtii CRL35. In the present paper, our goal is to study the effectiveness of this peptide and the producer strain in a murine model of pregnancy-associated listeriosis. A single dose of 5×10(9) colony-forming unit of L. monocytogenes FBUNT (Faculty of Biochemistry-University of Tucumán) resulted in translocation of pathogen to liver and spleen of BALB/c pregnant mice. The maximum level of Listeria was observed on day 3 postinfection. Interestingly, the intragastric administration of enterocin CRL35 significantly reduced the translocation of the pathogen to vital organs. On the other hand, the preadministration of E. mundtii CRL35 slightly inhibited this translocation. Listeria infection caused a significant increase in polymorphonuclear leukocytes at day 3 postinfection compared to the noninfected group. This value was reduced after the administration of enterocin CRL35. No significant changes were observed in either white blood cells or lymphocytes counts. Based on the data presented in the present work enterocin CRL35 would be a promising alternative for the prevention of Listeria infections.